Efeitos da ractopamina e da imunocastração de suínos nas características da barriga e na qualidade do bacon - Silva, Letícia Cristina Costa e [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The study evaluated the effects of immunocastration and the addition of ractopamine in the diet on the physical and chemical quality characteristics of belly and bacon from two crossbred pigs under different conditions of animal production, diet, management and slaughter. Five bellies for each treatment, totaling 60 bellies, were distributed in a 2x3 factorial arrangement using two levels of ractopamine in the diet, 0 and 7.5 ppm (for 21 days before slaughter) and three genders (gilts, immunocastrated males and castrated males) in a block design for the two genetics in different commercial farms. After carcass deboning, bellies were analyzed for length, width, firmness, belly thickness, fat thickness, chemical composition (protein, lipid, moisture, ash and carbohydrates), fatty acids profile, pH and objective color of meat and of fat, dry curing and process yields, during and after processing. After processing, analyzes of lean meat and fat percentage in bacon by digital image analysis, cooking loss, lipid oxidation, pH and objective color of meat and of fat (first day and 30 days after bacon processing) and sensory analysis for bacon odor and appearance were conducted. Bellies of barrow and immunocastrated pigs showed greater firmness, which can be an advantage for bacon processing and slicing. The immunocastrated animals had thicker bellies compared to the bellies of the gilts, however, the bellies of castrated did not differ from the others. Farm Bressiani had heavier bellies, longer lengths and widths, lower fat and higher primary area. The content of polyunsaturated fatty acids (total PUFA), linoleic acid (C18:2n6), linolenic acid (C18:3n3), arachidonic acid (C20:4n6), total omega-3 (n-3) and total omega-6 (n-6) were statistically higher for the immunocastrated pigs, and were higher than 0.4 for PUFA:SFA ratio, providing this belly of good nutritional quality. The bellies of gilts and immunocast ...
Keywords: Tecnologia de alimentos; Carne de porco - Industria; Suino - Alimentação e rações; Carne de porco - Qualidade; Físico-química; Processamento de imagens - Tecnicas digitais